Comparative analysis of the in-vitro antioxidant activity and bioactive compounds of flaxseed in China according to variety and geographical origin. (10th January 2018) - Deng, Qianchun; Yu, Xiao; Ma, Fangli; Xu, Jiqu; Huang, Fenghong; Huang, Qingde; Sheng, Feng
ABSTRACT: The present study aimed to use a chemometric study to compare the in-vitro antioxidant activities and bioactive compounds of flaxseed based on the variety and geographical origins, and further explore the specific components constructed the endogenous antioxidant system of flaxseed in China. The differential contents of α-linolenic acid (35.83–58.91%), lignans (11.37–33.31 mg/g), total phenolic acids (109.93–246.88 mg/100 g) and phytosterols (56.52–125.12 mg/g) of 32 flaxseed varieties were observed. Concomitantly, the in-vitro antioxidant activities varied from 32.56 to 46.22 mg TE/100 g, 0.58 to 1.08 mg TE/g, and 14.22 to 36.14 mmol TE/g as determined by the 2, 2'-diphenyl-1-picrylhydrazyl radical (DPPH), ferric reducing antioxidant power (FRAP) and 2, 2′-azinobis-(3-ethylbenzthiazoline 6-sulfonic acid) (ABTS) assays, respectively. Significant correlations were found between the antioxidant activities and contents of free syringic acid, p -coumaric acid glucoside and secoisolariciresinol diglucoside (SDG) ( p  < 0.01). Principal component analysis showed a relatively dispersed distribution between samples, which was not effective enough to determine the geographical origins of the flaxseed samples. Hierarchical cluster analysis allowed flaxseed samples to be grouped based on their in-vitro antioxidant activities and bioactive component contents, primarily in relation to variety specificity.